A review of application of ammonium polyphosphate as intumescent flame retardant in thermoplastic composites. (January 2016) - Lim, Kien-Sin; Bee, Soo-Tueen; Sin, Lee Tin; Tee, Tiam-Ting; Ratnam, C.T.; Hui, David; Rahmat, A.R.
Abstract: The application of ammonium polyphosphate (APP) in different types of commodity thermoplastic composites (polyethylene, polypropylene (PP), polystyrene (PS), poly(methyl methacrylate) (PMMA) and poly(ethylene terephthalate) (PET)) have been discussed in terms of mechanical properties, morphologies and thermal properties. In addition, engineering thermoplastics such as acrylonitrile-butadiene-styrene (ABS), polyamides and poly(vinyl alcohol) (PVOH) and their composites added with APP and other additives were analyzed as well. It was suggested that improvement of mechanical properties and morphologies of the thermoplastic composites could be made possible with appropriate amount of APP and other additives such as montmorillonite (MMT), pentaerythritol (PER) and different types of layered double hydroxide (LDH). Furthermore, thermal properties such as limiting oxygen index (LOI) values together with cone calorimetry and thermogravimetric analysis (TGA) performance could be enhanced through optimum combination of APP, PER and melamine which functions as intumescent flame retardant (IFR).